Budaya Organisasi Mempengaruhi Kinerja Karyawan CV. Air Mineral dalam Kemasan Aidrat Pondok Pesantren Sunan Drajat Banajarwati Paciran Lamongan - Siswadi, Siswadi; Rozikin, Ahamad Khaerul; Ariyanti, Fitri (Al-Muzdahir : Jurnal Ekonomi Syariah, 2023)
Culture in the organization can optimize the attitude of employees in acting according to the expectations and goals of the organization. The performance of an employee is individual, because each employee has a different level of ability in carrying out their duties. This research is a quantitative study, which aims to analyze the influence of organizational culture on the performance of CV employees. AMDK AIDRAT Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan. The research formulation consists of: 1) is there an influence of organizational culture on the performance of employees of CV. AMDK AIDRAT Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan?, and 2) how much influence does organizational culture have on employee performance at CV. AMDK AIDRAT Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan?. This study uses primary data and secondary data. The sample used is a saturated sample that uses all members of the population as a sample of 23 people. And the data collection techniques used are: Questionnaire (Questionnaire) and Documentation. As well as data analysis techniques used simple regression analysis and T test. The results of the analysis show that organizational culture influences the performance of CV employees. AMDK AIDRAT Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan. The results showed that it was suspected that there was a positive influence between organizational culture on the performance of employees at CV. AMDK AIDRAT Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan. And quite a big influence of organizational culture on the performance of CV employees. AMDK AIDRAT Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan so that the Organizational Culture in the company is very influential in improving the performance of CV employees. AMDK AIDRAT Pondok Pesantren Sunan Drajat Banjaranyar Paciran Lamongan.